Consumer Psychology Towards Corporate Social Initiatives: An Empirical Investigation - Singh, Anupam; Verma, Priyanka (Prabandhan: Indian Journal of Management, 2016)
Gradually, the world is recognizing the role of corporate responsibility towards society. Accordingly, there is a shift towards socially responsible behaviour around the world. This study attempted to address the question, whether social initiatives undertaken by a company influence the consumers' attitude towards it. For the said purpose, an empirical study was conducted to examine the impact of a company's CSR initiatives on consumers' trust and purchase behaviour. The effectiveness of social initiatives was measured on the basis of consumer attitude towards the factors such as subject, sincerity performance, and the value of assistance and cooperation provided. The results of our study revealed that consumers rewarded the companies that engaged in rehabilitation of appropriate social issues with due sincerity no matter how they provide social assistance to a social cause. There has always been buzz among the Indian companies about choosing and engaging in right social issues in order to gain consumers' favourable attitude. Thus, our study would assist managers to understand the consumers' psychology towards social initiatives, and would aid organizations in positioning themselves as socially responsible companies.